2001
DOI: 10.1002/1097-0215(20010520)95:3<140::aid-ijc1024>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Ser326Cys polymorphism inhOGG1 gene and risk of esophageal cancer in a Chinese population

Abstract: Ser326Cys polymorphism in the hOGG1 gene, which is involved in the repair of 8‐hydroxyguanine in oxidatively damaged DNA, has been identified and the variant genotype appears to be related to susceptibility to certain cancers. We investigated the association between Ser326Cys polymorphism and squamous‐cell carcinoma of the esophagus among a Chinese population. hOGG1 gene polymorphism was detected by PCR‐based single‐strand conformation polymorphism and DNA sequencing among 201 normal controls and 196 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 34 publications
3
77
1
Order By: Relevance
“…There have been studies showing an increased risk of esophageal squamous cell carcinoma in the presence of certain BER SNPs [12,29,31,32]. However, in our population of patients, we found no significant increase in risk for several individual BER SNPs or in a joint analysis under any model of inheritance.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…There have been studies showing an increased risk of esophageal squamous cell carcinoma in the presence of certain BER SNPs [12,29,31,32]. However, in our population of patients, we found no significant increase in risk for several individual BER SNPs or in a joint analysis under any model of inheritance.…”
Section: Discussioncontrasting
confidence: 86%
“…The SNPs were XPD Lys751Gln, XPD Asp312Asn, ERCC1 8092C/A, and ERCC1 118C/T in the NER pathway, and XRCC1 Arg399Gln, APE1 Asp148Glu and hOGG1 Ser326Cys in the BER pathway. Although a number of studies have examined a selection of these polymorphisms in relation to other cancers, including esophageal squamous cell carcinoma [28][29][30][31][32], an evaluation of these two pathways has not been reported comprehensively for esophageal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…DOI 10.1002/em well as metabolic homeostasis. In this regard, the Ser326Cys mutation has been associated with human lung squamous cell carcinomas [Lu et al, 1997;Chevillard et al, 1998;Sugimura et al, 1999;Wikman et al, 2000;Le Marchand et al, 2002;Paz-Elizur et al, 2003;Okasaka et al, 2009], orolaryngeal [Elahi et al, 2002], esophageal [Xing et al, 2001], kidney [Chevillard et al, 1998;Audebert et al, 2000Audebert et al, , 2002, and gastric cancers [Farinati et al, 2008]. Recently, two studies have also reported an association between the Ser326Cys mutation and increased body mass index and susceptibility to Type II diabetes [Daimon et al, 2009;Thameem et al, 2010].…”
Section: Nth1mentioning
confidence: 99%
“…[24][25][26][27] In order not to interfere with our analysis of hOGG1 polymorphism on the susceptibility to the pterygium, the subjects suffering from benign or malignant tumours were excluded. On the other hand, owing to the fact that the veterans accounted for approximately 50% of our patients, there were higher proportions of male sex and outdoor occupation type in our patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved in an Escherichia coli complementation assay 23 that the DNA repair activity of hOGG1-Cys 326 protein is lower than that of hOGG1-Ser 326 . The hOGG1 Cys/Cys homozygosity has been reported to increase the risks of lung cancer, 24 oesophageal cancer, 25 orolaryngeal cancer, 26 and stomach cancer. 27 Additionally, some studies revealed the impact of this genetic polymorphism on patients suffering from chronic oxidative stress.…”
Section: Introductionmentioning
confidence: 99%